Office spatial design attributes, sitting, and face-to-face interactions: Systematic review and research agenda. (January 2021) - Sugiyama, Takemi; Hadgraft, Nyssa; Clark, Bronwyn K.; Dunstan, David W.; Chevez, Agustin; Healy, Genevieve N.; Cerin, Ester; LaMontagne, Anthony D.; Shibata, Ai; Oka, Koichiro; Owen, Neville
Abstract: Office spatial design can affect the way workers move and interact in the workplace, which can have implications for health and productivity. This systematic review examined office spatial design attributes associated with sitting and face-to-face interactions (FTFIs) at work. The initial search using six databases (Art and Architecture Source; Business Source Complete; Ergonomics Abstracts; PubMed; Scopus; Web of Science) produced 2016 articles. After screening, 20 articles that met the inclusion criteria were reviewed. Of these, nine studies examined sitting, 10 studies examined FTFIs, and one study examined both. The following five design attributes were identified in these studies: office type; shared space; spatial layout; proximity of co-workers; and visibility of co-workers. Overall, the review found some evidence of office spatial attributes associated with workplace sitting or FTFIs. The studies reviewed suggested that workers in open-plan offices appear to have shorter overall sitting time and shorter bouts of sitting, compared to those in closed offices. Better visibility of workers was associated with shorter bouts of sitting. It was also found that proximity to co-workers was related to more frequent and longer FTFIs. These findings suggest that open-plan offices without visual barriers support shorter total sitting time and more frequent breaks of sitting. FTFIs are more likely to happen among workers whose workstations are close to each other. The review identified several gaps in the literature and proposed a research agenda to help advance the understanding of how to modify office spaces to encourage workers' movement and interactions. Highlights: - Twenty studies examining office spatial design were identified. - Shorter sitting time was observed in open-plan offices compared to closed offices. - Better visibility of workers was associated with shorter bouts of sitting. - Proximity to co-workers was associated with more and longer face-to-face interactions.